Staff’s experiences of implementing patient-initiated brief admission for adolescents from the perspective of epistemic (in)justice - Moberg, Jennie; Schön, Ulla-Karin (Frontiers in Psychiatry, 2022)
Background: The implementation of Patient-Initiated Brief Admission (PIBA) in child and adolescent psychiatry in Sweden is ongoing. This intervention enables adolescents between the ages of 13–17 and with complex mental health problems to initiate a short care period for relief and support rather than the care apparatus being controlling in this process. Offering it is likely to promote epistemic agency, an exchange of knowledge and recovery from mental health problems. Aim: The aim of this article is to explore the experiences of staff concerning obstacles and possibilities encountered in the implementation of PIBA in child and adolescent psychiatry and providing it to adolescents with complex mental health problems, but also how this intervention is sanctioned and the organizational conditions in place to implement a new way of working. Method: 27 employees, 21 women and six men, with various professions in child and adolescent psychiatry, were interviewed and the material was analyzed thematically. Result: Two overall themes emerged: ‘Staff’s Experiences of PIBA’ and ‘Managing Clinical PIBA Work’. The results were discussed in relation to the theoretical frameworks of epistemic injustice and Normalization Process Theory. The main findings indicate that PIBA was generally viewed in a positive way, but that obstacles arose when it was actually put into practice. Findings also point at an overall lack of agency among staff when implementing this new way of working, at the same time as the need to adapt PIBA from an adult psychiatric intervention to one for adolescents in child and adolescent psychiatry is addressed. Conclusions: This article offers insights into the views of psychiatric staff regarding the implementation of PIBA. If staff wish to support epistemic agency and recovery among adolescents, their agency may be an important aspect in the continued implementation. Furthermore, in order for PIBA to become normalized in a sustainable way, we suggest that the continued implementation should be characterized by a youth-friendly framework.